Inovasi Pengembangan Kawasan Wisata Hutan Pinus dalam Meningkatkan Pengunjung - Grace Sriati Mengga; Johana R. Tangirerung; Gustian Tandi Lolong; Ronald Rustan (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Lembang Buntu Datu has great natural tourism potential, especially the Buntu Datu Pine Forest area. This area has beautiful scenery, cool air, and charming mountain panoramas, so it has great potential to be developed as a leading tourist destination. However, in the development of the Buntu Datu Pine Forest tourist area, there are still several obstacles such as monotonous and unattractive tourist facilities, lack of lighting in the tourist area, lack of adequate cleaning facilities, and digital promotion that is not optimal. Therefore, observations of environmental conditions around tourism, observation of visitor behavior and community interaction with tourist areas, and in-depth interviews with tourism village managers (BUMDes), MSME actors, community leaders, and tourists to obtain information about what programs can be developed. From these results, in an effort to increase the number of visitors, tourist facilities such as tourist site signs, the creation of photo spots, the provision of garbage cans as supporting facilities, and the cleaning of tourist sites were made. In addition, efforts are also being made to empower the community and increase digital promotion so that the Buntu Datu Pine Forest tourist area is increasingly known and able to attract more tourists.